Answer:
y = 2
![(3)^(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/kvpro2tt48euee9q11pq6ui5jhjd49e4mx.png)
Explanation:
For the exponential function in the form
y = a
![b^(x)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/d79ov7qzyo2yilga4i73tf3wtr8kbr2yha.png)
Use ordered pairs from the table to find a and b
Using (0, 2 ), then
2 = a
(
= 1 ) , thus
a = 2, so
y = 2
![b^(x)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/d79ov7qzyo2yilga4i73tf3wtr8kbr2yha.png)
Using (1, 6 ) , then
6 = 2b ( divide both sides by 2 )
b = 3
Thus the exponential function is
y = 2
![(3)^(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/kvpro2tt48euee9q11pq6ui5jhjd49e4mx.png)